First Order System of Equations of Mixed Type and Second Order Equation of Mixed Type (Journal of Partial Differential Equations, 1993)
A system of first order equations of mixed type, which may be reduced to a general second order equation of mixed type, is considered. Uniqueness of solution to the generalized Tricomi problem is proved by the method of auxiliary function. Existence of H&sup1 strong solution is based on a characteristic problem and is proved by the Fredholm's alternative properties.